Air, Air Everywhere!. Issue 12 (20th August 2020) - Kanji, Rafiq; Patel, Kayur; Stangoe, Douglas
Abstract: When using a gum elastic bougie, a common device to aid difficult intubations, one must appreciate the significant consequences, be prepared to manage emergency complications, and use safely by advancing under direct vision and using the markings to guide insertion. Abstract : When using a gum elastic bougie, a common device to aid difficult intubations, one must appreciate the significant consequences, be prepared to manage emergency complications, and use safely by advancing under direct vision and using the markings to guide insertion.